CCL2 as a potential therapeutic target for clear cell renal cell carcinoma. (26th September 2016) - Arakaki, Ryuichiro; Yamasaki, Toshinari; Kanno, Toru; Shibasaki, Noboru; Sakamoto, Hiromasa; Utsunomiya, Noriaki; Sumiyoshi, Takayuki; Shibuya, Shinsuke; Tsuruyama, Tatsuaki; Nakamura, Eijiro; Ogawa, Osamu; Kamba, Tomomi
Abstract : Antiangiogenic‐targeted therapies are used for treatment of advanced renal cell carcinoma. Our clinical data, corroborated by xenograft models, suggest that CCL2 is involved in tumor progression and may serve as novel therapeutic target for clear cell renal cell carcinoma. Abstract: We previously reported that the pVHL‐atypical PKC‐JunB pathway contributed to promotion of cell invasiveness and angiogenesis in clear cell renal cell carcinoma (ccRCC), and we detected chemokine (C‐C motif) ligand‐2 (CCL2) as one of downstream effectors of JunB. CCL2 plays a critical role in tumorigenesis in other types of cancer, but its role in ccRCC remains unclear. In this study, we investigated the roles and therapeutic potential of CCL2 in ccRCC. Immunohistochemical analysis of CCL2 expression for ccRCC specimens showed that upregulation of CCL2 expression correlated with clinical stage, overall survival, and macrophage infiltration. For functional analysis of CCL2 in ccRCC cells, we generated subclones of WT8 cells that overexpressed CCL2 and subclones 786‐O cells in which CCL2 expression was knocked down. Although CCL2 expression did not affect cell proliferation in vitro, CCL2 overexpression enhanced and CCL2 knockdown suppressed tumor growth, angiogenesis, and macrophage infiltration in vivo. We then depleted macrophages from tumor xenografts by administration of clodronate liposomes to confirm the role of macrophages in ccRCC. Depletion of macrophages suppressed tumor growth and angiogenesis. To examine the effect of inhibiting CCL2 activity in ccRCC, we administered CCL2 neutralizing antibody to primary RCC xenografts established from patient surgical specimens. Inhibition of CCL2 activity resulted in significant suppression of tumor growth, angiogenesis, and macrophage infiltration. These results suggest that CCL2 is involved in angiogenesis and macrophage infiltration in ccRCC, and that CCL2 could be a potential therapeutic target for ccRCC.